Contaminación visual urbana y su consecuencia en la salud de la población en la zona central del distrito de San Juan, Región Loreto, 2023 - Barco Navarro, Siegfried Luis (2023)
This thesis shows a cause-effect relationship of visual pollution in the residents of San Juan Bautista, through a quantitative survey design, non-experimental transversal descriptive type, and sample design of a population of 110 families. After the application of the survey, it is concluded that there is misinformation in the population, in the concepts of visual pollution, so problems such as the presence of wiring, street commerce, painting of houses, garbage dumps, are factors that influence the alteration of the urban landscape of the city, and the deterioration of the natural landscape that the city of Iquitos can offer us, as a jungle area. The consequences that these problems generate in the population are anger and irritability, discomfort and distraction, related factors that can cause stress symptoms, which affect the development of people's daily activities.